6(2x-5)=5(3x+7)

Simple and best practice solution for 6(2x-5)=5(3x+7) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(2x-5)=5(3x+7) equation:


Simplifying
6(2x + -5) = 5(3x + 7)

Reorder the terms:
6(-5 + 2x) = 5(3x + 7)
(-5 * 6 + 2x * 6) = 5(3x + 7)
(-30 + 12x) = 5(3x + 7)

Reorder the terms:
-30 + 12x = 5(7 + 3x)
-30 + 12x = (7 * 5 + 3x * 5)
-30 + 12x = (35 + 15x)

Solving
-30 + 12x = 35 + 15x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-15x' to each side of the equation.
-30 + 12x + -15x = 35 + 15x + -15x

Combine like terms: 12x + -15x = -3x
-30 + -3x = 35 + 15x + -15x

Combine like terms: 15x + -15x = 0
-30 + -3x = 35 + 0
-30 + -3x = 35

Add '30' to each side of the equation.
-30 + 30 + -3x = 35 + 30

Combine like terms: -30 + 30 = 0
0 + -3x = 35 + 30
-3x = 35 + 30

Combine like terms: 35 + 30 = 65
-3x = 65

Divide each side by '-3'.
x = -21.66666667

Simplifying
x = -21.66666667

See similar equations:

| 7(4x+1)=5(4x+3) | | 3(5-4x)=3(3x+4) | | 5(X+3)+(2X-7)=3X-9 | | 1/3,47/6 | | 82-k=37 | | x^2-3x+62=0 | | 240=x+75 | | 5x-7=2x-67 | | X+4(4x+16)=21 | | 9(n+1)=3(n-5) | | 4x+50=130 | | (5w-8)(9-w)=0 | | y=x^2-2.4x-2.2 | | -5(-8x+5)+3x=-369 | | (W+2)(w-5)= | | 2y+10=3y | | 0=2w^2-3w-44 | | 8(-8+8k)=-192 | | 4c-2(x-3)=-2+5x-10 | | 16+8=40 | | 6-6x+5x=13 | | (m-n+k)(m+7n-6k)=0 | | 4(-2+8n)=-136 | | X+2x+7x+9x+1=42 | | 14=21b | | 4(3-2x)=3(2-3x) | | -8=-2n | | -50=5d | | 135=-9k | | 3/4*x=2/7 | | 25x+71=156 | | 4(7x+8)+x=206 |

Equations solver categories